2018
DOI: 10.4172/2157-7439.1000520
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer Grafting onto (on) and into (in) Pegylated Gold Nanoparticles: Physicochemical Characterization and In vitro Cytotoxicity Investigation in Renal Cells

Abstract: Gold Nanoparticles (AuNPs) have already a remarkable interest as viable biomedical materials. Additionally, the strategy of using biomolecules to modify their surface properties is a very attractive as it leads to the generation of new nanometric hybrid materials. In this respect, aptamers, functional small single-strand oligonucleotides (DNA or RNA), are ideal candidates for molecular targeting applications since the high affinity to their target molecules. Thus, the urge of new and effective methodologies to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 64 publications
2
8
0
Order By: Relevance
“…44 Recently, we have functionalized and characterized a renal aptamer on pegylated gold nanoparticles (PEG-AuNPs) by two chemical conjugations. 24 Previously, Dam et al 45 showed that loading of aptamer AS1411 onto AuNPs could be regulated through the charge of the ligands and pH. In our case, the loading of APT onto PEG-AuNPs was confirmed by the absorption peak at 260 nm from APT (Figure S2, Supporting Information).…”
Section: Aptamer Loading Onto Pegylated Gold Nanoparticles (Apt On Pe...supporting
confidence: 64%
See 3 more Smart Citations
“…44 Recently, we have functionalized and characterized a renal aptamer on pegylated gold nanoparticles (PEG-AuNPs) by two chemical conjugations. 24 Previously, Dam et al 45 showed that loading of aptamer AS1411 onto AuNPs could be regulated through the charge of the ligands and pH. In our case, the loading of APT onto PEG-AuNPs was confirmed by the absorption peak at 260 nm from APT (Figure S2, Supporting Information).…”
Section: Aptamer Loading Onto Pegylated Gold Nanoparticles (Apt On Pe...supporting
confidence: 64%
“…This value confirms the aptamer length. 24 Moreover, ζ-potential measurements confirm the stability of PEG-AuNPs and APT PEG-AuNPs at physiological pH (ζ-potential = −28 ± 1 MV, −30 mV for APT ON PEG-AuNPs and −33 ± 1 mV for APT IN PEG-AuNPs) (Table 1). This stability was improved by the presence of the PEG coating.…”
Section: Aptamer Bioconjugationmentioning
confidence: 72%
See 2 more Smart Citations
“…In the latest years, Spadavecchia et al have in-depth investigated the synthesis of hybrid nanoparticles based on drugs and/or biomolecules-gold-complex by an experimental approach named "Method IN", in which the drugs or biomolecules interact actively with gold salt (HAuCl 4 ) by chelation bonding. A biocompatible polymer molecule (PEG diacid) acts as surfactant, in order to form hybrid gold nanoparticles upon reduction by NaBH 4 [10][11][12].…”
Section: Introductionmentioning
confidence: 99%